Central America : Structural Foundations for Regional Financial Integration. (International Monetary Fund, 2006)
Intraregional financial activity in Central America has grown substantially in the past decade, contributing to efficiency and economic development. At the same time, the expansion of activities by regional conglomerates has increased the challenges to supervisory authorities of containing the risks of contagion. Prepared as part of the Central America Financial Sector Regional Project by an IMF and World Bank staff team, this book outlines trends in the region's financial sector integration, supervisory responses, development of the insurance sector, payment and securities settlement arrangements, and worker remittances. It addresses the many common policy challenges facing Central American countries--Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, and Panama--in financial sector reform. The book offers key policy recommendations.